Olfaction in mosquito-host interactions (John Wiley and Sons, 1995)
Mosquito-borne parasitic diseases are major health problems in many developing countries. A clear understanding of olfactory-mediated mosquito—host interactions is a prerequisite for any malaria control strategy based on disrupting mosquito olfactory-mediated behaviour. The book begins with a general overview of mosquito life cycle styles and how odour-mediated host location fits into the repertoire of behaviours that a specific species may exhibit. The general notion of now the physiological state of the mosquito can affect host-locating behaviour is discussed, together with the role of odour in mosquito orientation and other aspects of mosquito behaviour. Certain aspects of insect olfaction and its underlying physiological mechanisms are incorporated within this book. These include a discussion of the functional organization of the neural pathways mediating olfaction, and detailed data of the structure and physiology of mosquito olfactory receptor cells and the molecular biology of the receptor transduction process. Receptors for non-host-related odours and their relationship to host-locating behaviour are also discussed. The principal focus of this symposium is on the ways in which our knowledge of olfactory-mediated mosquito—host interactions might be used in mosquito control programmes. Therefore, a continuing theme throughout the discussions is the evaluation of data in relation to the development of such control programmes in the future.
Ciba Foundation symposium ; 200
Keywords: Malaria; Mosquito Control; Olfactory Pathways; Insect Repellents; malárie; Sensory Receptor Cells; Odorants; Disease Vectors; moskyti - kontrola; infekce přenášené vektorem; infekční lékařství; čichové dráhy; odoranty; nervové receptory; repelenty proti hmyzu